Hubbil Khair PERSPEKTIF PENDIDIKAN DALAM PENERAPAN KARAKTER DI LINGKUNGAN KELUARGA - Hubbil Khair (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2020)
Family is the first and main place where a child is educated and grew up. The function of family as a vehicle for educating, nurturing, and socializing children, developing the abilities of all its members so that they can carry out their functions in society well, as well as providing satisfaction and healthy environment to achieve a prosperous family and a place for the formation of the main character of children, especially in the early days of their growth as human. Character education is a transformation of life values to be developed in a child's personality. The world of education is expected to be a booster to facilitate character building so that family members have awareness of a harmonious and democratic life of nation and state while still paying attention to the norms in society that have become a mutual agreement. Keywords : Perspective, Character Education, Family